Inflammatory Bowel Disease Registry and Monitoring: Feasibility Study and Application (Isfahan Inflammatory Bowel Disease Surveillance Project) - Baghaei, Abdolmehdi (Int J Prev Med, 2019)
BACKGROUND: Inflammatory bowel disease (IBD) incidence has been increased in Iran as a developing country. Surveillance is a standard method for accessing valid data about disease epidemiology to make relevant decisions for disease control, prevention, and management. We designed Isfahan IBD Surveillance Project (IISP) to make a surveillance system in this area. METHODS: The project is designed in 3 phases. At the first phase, a model of step-wise approach (core, expanded core, and optional variables) for IBD surveillance was designed and implemented among IBD patients registered at a major referral gastrointestinal diseases clinic in Isfahan. Data bank program and its software were designed with suitable and multifunctional features. A total of 352 IBD cases were registered to data bank and analyzed as a pilot study of IISP. RESULTS: A total of 352 IBD patients, including 245 ulcerative colitis (UC), 80 Crohn's disease (CD), and 27 indeterminate colitis, were registered to the data bank. Bloody stool and abdominal cramp were the most common presentation symptom among UC and CD, respectively. Extensive pancolitis was the most prevalent phenotype (40%) of UC. Over two-thirds of our IBD patients were in remission states. Biologic agents had been prescribed in about 10% of patients during disease. Primary sclerosing cholangitis was detected in about 7% and 10% of CD and UC patients, respectively. CONCLUSIONS: Valid data from a standard surveillance system are a relevant, trustworthy tool for making decision by health policy-makers. Integrated comprehensive interventional programs for disease control and management is the second phase of IISP.